Autosomal dominant hyper‐IgE syndrome: When hematopoietic stem cell transplantation should be considered?. (4th June 2020) - Oikonomopoulou, Christina; Goussetis, Evgenios
Abstract: AD‐HIES or Job's syndrome is a primary immunodeficiency, caused by dominant negative mutations in signal transducer and activator of transcription (STAT) 3. The syndrome is characterized by infectious, immunologic, and non‐immunologic manifestations and is associated with significant morbidity, mortality, and development of lymphomas. What has not yet been elucidated is the role of HSCT in the disease treatment spectrum. We review published cases of patients with AD‐HIES that underwent HSCT and attempt to clarify at what stage HSCT should be considered and what are the complications.